The Influence of Chemopoly Learning Media on Learning Motivation of Class XII Students on Elemental Chemistry Material - Zanah, Lusi Miftahul; Sumiati, Tina Endah; Affifah, Isriyanti; Santuso, Edy; Kusumawati, Adline Charfian; Hartati, Ajeng (Jambura Journal of Educational Chemistry, 2024)
This research aims to determine the effect of the Chemopoly learning media on increasing the learning motivation of class Students feel bored and dissatisfied with the delivery of material or giving assignments conventionally, especially when the chemistry subject is in the last class period. By implementing the Chemopoly learning media, students' learning motivation increases in chemistry subjects. Apart from that, Chemopoly learning media also increases understanding of concepts in the material provided by the teacher. The method used in this research is qualitative method. The type of research used is a qualitative descriptive approach. The research was conducted at SMA Negeri 8 Serang City with research subjects of class XII IPA 2 students totaling 37 students. The data collection techniques used are, observation, questionnaires and documentation. The research results showed that students' learning motivation increased after implementing the Chemopoly learning media. Students feel that learning chemistry is more fun and less monotonous after using Chemopoly learning media. Students also want the Chemopoly learning media to be applied to other subjects so that learning no longer uses conventional methods.